Characteristics of Contemporary Methodologies of Classic Homeopathy - Madsen, Ruy (Homœopathic Links, 2019)
In the early 21st century, the methodologies of Massimo Mangialavori, Rajan Sankaran and Jan Scholten stood in classic homeopathy. These authors criticise the traditional methods of case analysis and propose new instruments to the search for the most appropriate remedy. These contemporary methodologies present common points: the study of themes, classification in groups, interrelation of substance-remedy-patient and predictive character. These characteristics were already presented by other authors throughout the history of homeopathy, but they were only systematised as a practical instrument in the past decades.
Keywords: classic homeopathy; contemporary methodologies; methodology of complexity; element theory; sensation method